ANALYSIS OF CASUAL CONVERSATION IN SPONTANEITY, INTERACTIVITY, INTERPERSONALLY AND COHERENCE FEATURES - Nur Ekaningsih (Indonesian EFL Journal, 2019)
This study was carried out to respectively illustrate the casual conversation features in terms of spontaneity, interactivity, interpersonally, and coherence. The casual conversation analyzed was a conversation of two non-native English speakers who are an English teacher and a student at a convenient situation. The conversation lasted for eighteen minutes was transcribed. Results showed that S1 dominantly used features of spontaneity on the field of repetition, incomplete utterances, and chunks. On the features of interactivity, S2 is more cooperative than S1. In addition, on the feature of interpersonally, both speakers seemed to appeal more agreement. Thus, in terms of coherence, both speakers can run the conversation smoothly. The two speakers were still making conversation in line with the topic although they changed the topic three times.